Effects of an alkali-acid purification process on the characteristics of eucalyptus lignin fractionated from a MIBK-based organosolv process. Issue 95 (28th September 2016) - Klamrassamee, Thepparat; Tana, Tana; Laosiripojana, Navadol; Moghaddam, Lalehvash; Zhang, Zhanying; Rencoret, Jorge; Gutierrez, Ana; del Rio, José C.; Doherty, William O. S.
Abstract : In this study, the effects of an alkali-acid purification process on the properties of eucalyptus lignin isolated from a methyl isobutyl ketone (MIBK)/methanol/water-based organosolv fractionation process were evaluated. Abstract : In this study, the effects of an alkali-acid purification process on the properties of eucalyptus lignin isolated from a methyl isobutyl ketone (MIBK)/methanol/water-based organosolv fractionation process were evaluated. The results showed that the treatment reduced the content of carbohydrates, ash, nitrogen and sulfur, and improved lignin solubility (up to 218%) in five organic solvents (acetone, methanol, ethanol, tetrahydrofuran and dimethyl sulfoxide) and removed lignin fractions with smaller molecular weights. However, analysis by Py-GC/MS, solid state NMR and 2D-HSQC NMR indicated that the alkali-acid treatment process did not cause changes to the monomeric lignin subunits and linkages of the lignin polymer. The treated lignin showed slightly higher thermal stability at temperatures <250 °C, though its maximum rate of decomposition occurred at 325 °C, 26 °C lower than that of the untreated lignin. On the basis of these results, the significant improvement in solvent solubility of the lignin by the treatment process will widen lignin application.